CHOICE OF OPTIMAL INTERBLOCK ELECTRIC CONNECTONS DESIGN FOR ELECTRONIC MEANS - Yefimenko А. А. (Radio Electronics, Computer Science, Control, 2011)
Models and algorithms are proposed for choosing a design of electric contacts by the criteria of cost and labor expenditures as well as quality and efficiency indices, which permit to optimize the electronic means engineering process.